SELECTION OF SUGARCANE FAMILIES BY MIXED MODELS - OLIVEIRA, Ricardo Augusto de; DAROS, Edelclaiton; BESPALHOK FILHO, João Carlos; ZAMBON, José Luis Camargo; IDO, Oswaldo Teruyo; WEBER, Heroldo; RESENDE, Marcos Deon Vilela de; ZENI NETO, Hugo (Scientia Agraria, 2008)
The objectives of this work were to select superior families and parents of sugarcane originated from biparental crosses, for biomass production using mixed models: REML/BLUP. The REML/BLUP methodology was adopted, with the REML used for estimation of the genetic variance, and the BLUP for the estimation of genetic values of families. For this study, 80 full-sib families from RB03 series were used, originated from crosses made on Serra do Ouro Station, County of Murici, Alagoas, in 2003. The experiment was installed in an experimental area, County of São Tomé, Paraná. The experimental design used was incomplete blocks, with five replications per family. Each replication was composed by ten plants. For selection of superior families, tons of canes per hectare (TCH) were considered. According to the obtained results, the analyzed characters showed individual heritabilities () from medium magnitudes (0.22), while the heritabilities from family means () ranged from 0.73. The selection of families with genotypic values greater than the average trial, it is estimated significant profits of TCH. Based on TCH the best families were RB825336 e SP80-1816, RB825548 e RB855156, SP80-3280 e RB845257, RB83102 e RB855113, RB8495 e RB835089.